Design of an Arduino-Based Inverse Type Overcurrent Relay - susilo, rizky; Marselino Pakorong; Priyo Handoko Chusnama Ali (Emitor: Jurnal Teknik Elektro, 2025)
Abstract An overcurrent relay is an important device in protection systems to protect electrical equipment from damage caused by excessive overcurrent. The objective of this study is to design and implement an overcurrent relay system that can detect and mitigate overcurrent using the inverse time protection principle, developed using the popular and accessible Arduino platform. An overcurrent relay (OCR) is an electrical protection device that operates based on overcurrent detection. There are two main characteristics, namely inverse time and constant time.Inverse Time Relay cuts off overcurrent with an operating time that increases as the current increases, while Constant Time Relay has a fixed operating time. This research discusses the working principles, differences in characteristics, and applications of both types of relays to improve the effectiveness of protection in electrical power systems.